TOWARDS THE MODELING OF GLACIER MICROTOPOGRAPHY USING HIGH-RESOLUTION DATA FROM UNMANNED AERIAL SURVEY - I. V. Florinsky; T. N. Skrypitsyna; D. P. Bliakharskii; O. T. Ishalina; A. S. Kiseleva (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
Glaciated areas are important targets for interdisciplinary research. In the last quarter of the 20th century, there has been a significant shift in glacier observation approaches from direct fieldwork to remote sensing. Over the past 15 years, unmanned aerial systems have been increasingly used for this purpose. In this article, we briefly describe a newly launched Russian–Chinese project aimed at developing a theory and methodology for digital modeling and analysis of the glacier microtopography using very high resolution data from unmanned aerial surveys. We argue the relevance of the study and review key publications on the application of digital terrain modeling and geomorphometry in glaciology. Next, we discuss the aim of the project and tasks performed by the Russian side, as well as materials and methods used in the study. As initial data, we use multi-temporal, digital aerial images of very high resolution (5 cm) collected by the unmanned aerial survey of the ice sheet and glaciers near the Larsemann Hills, East Antarctic. Finally, we present some examples for geomorphometric analysis of glacier microtopography including snow/ice features of eolian origin.